Application of humanized mice in the safety experiments of antibody drugs - Zhimin Sun; Mengyun Gu; Zixuan Yang; Lei Shi; Liyuan Zhao; Minhui Zheng; Yan Wang; Wei Zhang; Kexin Han; Naping Tang (Animal Models and Experimental Medicine)
Abstract Therapeutic antibodies are valued for their high specificity and selectivity in immunotherapy. However, the potential toxicity they may elicit underscores the necessity of assessing their preclinical efficacy and safety using suitable animal models. In this context, we review the various categories and applications of humanized mice, which have been engrafted with human cells or tissues to mimic the human immune system. These models are extensively utilized in the nonclinical assessment and development of various antibody drugs, acting as a conduit to clinical research. However, several challenges remain, including the limited lifespan of humanized mice, inadequate engraftment of human cells, and the rudimentary nature of the immune environment in these models. The development of humanized immune system models in mice presents both opportunities and challenges, potentially leading to new insights into the evolution and application of antibody therapeutics.